Percepção visual da cidade: iconografias da natureza urbana de Belém (1808 – 1908) - PEREIRA, Rosa Claudia Cerqueira (Universidade Federal do Pará, 2015)
This study proposes an analysis of urban iconography of Belém, produced during the nineteenth and early twentieth centuries. The thesis aims to analyze the representation of nature in Belém, specifically in the years 1808 to 1908. The initial commitment of the thesis concentrated on researching the various types of iconography of Belém during the nineteenth century. The questions that sought to highlight deal on how travelers seized the city in his visit to Belém, both from a narrative point of view as the visual until the year 1890. From then also identify how governments have promoted the city beyond the Amazon region. Brazilian nature It is observed that came to be represented, from the nineteenth century, through written and iconographic, that thanks to the influence of scientism and romantic artistic sensibility that permeated the knowledge of the country. The romantic sensibility made the relationship between science and esthetic to apprehend and represent nature in an overall view, inaugurating a new conception of landscape and trying to "invent" and view an urbane nature, which is the main theme of this study; is the phenomenon of urbanization, which was registere, especially by means of photography. In this type of photos, nature appears domesticated, adapted to urban design, its artful and geometric shape is valued. Urban photography from the late nineteenth century reintroduces the "ideal beauty" in the nature of the images ordered on the model of French gardens, English and Italian From assumption that contemplation of nature is adapted to the reality of the Amazon region, although they were present models from Europe. The perception of nature in the Amazon the second half of the nineteenth century, the influence of new ways of conceiving the nature were designed to cities in the redesign of spaces to form the green area, especially in Belém.. To think historically the representation of nature is to reflect on its appropriation by human action while different individuals and social groups circulated and left their specific marks in places built from a domesticated nature in the urban landscape.